2021
DOI: 10.1007/s00394-021-02565-5
|View full text |Cite
|
Sign up to set email alerts
|

The associations of the Palaeolithic diet alone and in combination with lifestyle factors with type 2 diabetes and hypertension risks in women in the E3N prospective cohort

Abstract: as well as a subsidy from the "Ministère de l'enseignement supérieur, de la recherche et de l'innovation" for public service charges under the reference n°2102 918823.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…This meta-analysis found that even with short-term consumption, the PD contributed to normalizing blood pressure, improving lipid profile, with a reduction in total cholesterol (TC), TG, and LDL-C and increased HDL-C, sensitivity to insulin and glucose tolerance, and decreased body weight, fat mass, and WC. These results were also confirmed by Shah et al ( 19 ) in a French prospective study, in which the PD and adherence to a Paleolithic lifestyle proved to be favorable alternatives for the prevention of type 2 diabetes and hypertension. Furthermore, it has been suggested that adherence to the PD was associated with a lower chance of systemic inflammation and oxidative stress ( 30 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This meta-analysis found that even with short-term consumption, the PD contributed to normalizing blood pressure, improving lipid profile, with a reduction in total cholesterol (TC), TG, and LDL-C and increased HDL-C, sensitivity to insulin and glucose tolerance, and decreased body weight, fat mass, and WC. These results were also confirmed by Shah et al ( 19 ) in a French prospective study, in which the PD and adherence to a Paleolithic lifestyle proved to be favorable alternatives for the prevention of type 2 diabetes and hypertension. Furthermore, it has been suggested that adherence to the PD was associated with a lower chance of systemic inflammation and oxidative stress ( 30 ).…”
Section: Discussionsupporting
confidence: 76%
“…The Paleolithic diet score was constructed as discordance between diet during the Paleolithic period and the present era (17,18). However, considering the cumulative association between diet and lifestyle factors, studies have used this score alone or in combination with lifestyle factors (Paleolithic-like lifestyle score) in relation to the incidence of some chronic diseases and mortality, showing inverse associations (17)(18)(19). However, studies investigating the relationship between these scores in the NAFLD are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Longer duration RCTs with larger sample sizes are needed, but one large‐scale epidemiological study used 20 years of prospective data on more than 70,000 women, applying a “Paleolithic diet score” and a “Paleolithic‐like lifestyle score” (physical activity, smoking status, and BMI) to baseline data. The PTD predicted T2DM and HTN risk, but the combined diet and lifestyle scores predicted them more strongly 170 …”
Section: Randomized Control Trials and Other Clinical Trials Of Hg‐li...mentioning
confidence: 87%
“…The PTD predicted T2DM and HTN risk, but the combined diet and lifestyle scores predicted them more strongly. 170…”
Section: Randomized Control Trials and Other Clinical Trials Of Hg-li...mentioning
confidence: 99%
“…Accumulating evidence has suggested that diet, behavior, or lifestyle play a significant role in the development and progression of hypertension [4,5]. Sleep-disordered breathing (SDB) is one of the important factors attracting researchers’ attention, especially among Chinese.…”
Section: Introductionmentioning
confidence: 99%